Legal Study on The Requirements for Foreign Capital Investment in The Industrial Sector in Indonesia - Marpaung, Jonathan (Syntax Corporation, 2024)
This study examines the legal requirements governing foreign capital investment in the industrial sector in Indonesia. This study uses a normative legal approach. The data collection technique in this study is through literature studies. The data that has been collected is then analyzed in three stages, namely data reduction, data presentation and drawing conclusions. The results of the study show that the requirements for foreign capital investment in the industrial sector in Indonesia are regulated in Article 5 of Law Number 25 of 2007. Foreign Investors are required to be in the form of a limited liability company and must be located within the territory of the Republic of Indonesia, unless otherwise regulated by law. Investors, both domestic and foreign, can invest in the form of a limited liability company. Foreign Investors are only allowed to carry out business activities in large sectors with an investment value exceeding IDR 10,000,000,000.00 (ten billion rupiah), excluding the value of land and buildings. In addition, they must also complete the licensing or establishment documents required for foreign investors. Strong legal protection is needed to create a comfortable atmosphere for foreign investment in the Capital City of the Archipelago (IKN). The regulations applied must maintain the sovereignty of the nation and not betray the values adopted by the state. Effective legal protection will provide certainty and trust for foreign investors, so that they can contribute positively to economic growth and infrastructure development in Indonesia.